Highlighting gaps in technology acceptance research: A call for integrating happiness and well-being into smart city development - Anton Manfreda; Tea Mijač (Journal of Innovation & Knowledge (JIK), 2024)
Today's world is dealing with various challenges such as global warming, overpopulation, resource allocation, uneven economic development and many others. Most of these issues are not novel; however, since the number of global populations living in urban areas is expected to increase, these problems will become more and more difficult to manage. Some of these challenges and issues refer to fast urbanization, old infrastructure or the difficulty of properly managing new technologies in cities. Smart city initiatives are frequently viewed as solutions to these challenges, but the reliance on technology alone may be misleading. Despite the widespread adoption of advanced technologies in urban areas to overcome several problems, there is a lack of research on their impact on residents' overall well-being and happiness. Our paper addresses this gap by critically evaluating existing technology acceptance models, which have primarily focused mostly on usage intention and use behaviour, to identify their limitations in addressing the complex effects of technology on well-being. The aim was therefore to explore the extent to which technology can contribute to increased happiness in smart cities and how existing research streams address this relationship. To achieve our aim, we employ a mixed-methods approach, namely integrating the IMD Smart City Index and Happy City Index to explore the connection between 'smartness' and 'happiness' a scoping review and bibliographic analysis of over 5000 papers on technology adoption, complemented with an empirical survey of 193 millennials on their attitudes towards smart technology and well-being. Through an extensive literature review, this paper highlights the overlooked research on smart city to improve well-being by proposing that future research should focus on expanding technology acceptance frameworks that should include measures for happiness and well-being. Our findings highlight the importance for continued research into the impact of technology on well-being and the necessity for a holistic approach that merges technological advancements and well-being in smart city development. This study emphasizes the need for future research to expand technology acceptance frameworks to include measures for happiness and well-being, providing a more comprehensive understanding of the role of technology in enhancing urban life.
Keywords: 650; Smart cities; Technology acceptance; Well-being; Happiness; Smart city index; Happy city index